The political economy of unfinished development projects: corruption, clientelism, or collective choice? - Williams, M (Cambridge University Press, 2017)
Development projects like schools and latrines are popular with politi- cians and voters alike, yet many developing countries are littered with half-finished projects that were abandoned mid-construction. Using an original database of over 14,000 small development projects in Ghana, I estimate that one-third of projects that start are never completed, con- suming nearly one-fifth of all local government investment. I develop a theory of project non-completion as the outcome of a dynamically incon- sistent collective choice process among political actors facing commitment problems in contexts of limited resources. I find evidence consistent with key predictions of this theory, but inconsistent with alternative explana- tions based on corruption or clientelism. I show that fiscal institutions can increase completion rates by mitigating the operational consequences of these collective choice failures. These findings have theoretical and methodological implications for distributive politics, the design of inter- governmental transfers and aid, and the development of state capacity.